2009
DOI: 10.1111/j.1468-0289.2009.00488.x
|View full text |Cite
|
Sign up to set email alerts
|

Profitability trends in Hollywood, 1929 to 1999: somebody must know something1

Abstract: This article presents an overview of the development of the US film industry from 1929 to 1999. Notwithstanding a volatile film production environment, in terms of rate of return and market share variability, the industry has remained relatively stable and profitable. Film production by the film studios is interpreted as analogous to the construction of an investment portfolio, whereby producers diversified risk across budgetary categories. In the 1930s, high‐budget film production was relatively unprofitable,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…These are highly skewed, with a small number of large revenue films coexisting alongside considerably greater numbers of smaller revenue films. Moreover, the skewed nature of these distributions appears to be an empirical regularity, with Pokorny and Sedgwick [17] dating this phenomenon back to at least the 1930s, making it an early example of a mass market long tail. Indeed, De Vany and Walls [5,6] commented on the consequential difficulty in modelling the dispersion, skewness and kurtosis of film revenues.…”
Section: Introductionmentioning
confidence: 95%
“…These are highly skewed, with a small number of large revenue films coexisting alongside considerably greater numbers of smaller revenue films. Moreover, the skewed nature of these distributions appears to be an empirical regularity, with Pokorny and Sedgwick [17] dating this phenomenon back to at least the 1930s, making it an early example of a mass market long tail. Indeed, De Vany and Walls [5,6] commented on the consequential difficulty in modelling the dispersion, skewness and kurtosis of film revenues.…”
Section: Introductionmentioning
confidence: 95%
“…A parallel development in Hollywood at that time was that tickets admissions started to decline in the early 1960s and reached an all-time low by the end of the decade (Pokorny & Sedgwick, 2010). By the late 1960s, declining admissions and the surprising box office success in the United States of some novel European films, like Michelangelo Antonioni's Blow Up, had shaken the studios' confidence in their ability to understand what moviegoers wanted.…”
Section: Historical Evolution Of Directorial Careers In the Filmmakinmentioning
confidence: 99%
“…Pokorny and Sedgwick (2010) found that since the 1930s the financial performance of U.S. films has remained unpredictable and volatile, and Ravid (1999) and De Vany and Walls (2004) found that the presence of star directors and actors in a film does not reduce the inherent uncertainty about its financial performance. In an analysis of 175 randomly selected films released between 1991 and 1993, Ravid (1999) found that their budgets ranged from US$1 million to US$70 million (M = US$15.67 million, SD = 13.90 million), and their domestic revenues (U.S. gross) ranged from US$6,000 to over US$162 million (M = US$22.09 million, SD = 32.795).…”
Section: Patterns Of Productivity Creativity and Financial Performancementioning
confidence: 99%
“…While sales no doubt would have been higher without the depression, the largest studios remained profitable and the rest returned to profitability by the mid‐1930s (Schatz ). In fact, the late 1930s and 1940s, after sound was introduced but prior to wide television ownership, represent the high water mark for real expenditures on movie theater admissions (Pokorny and Sedgwick ).…”
Section: Datamentioning
confidence: 99%